Applicability of pediatric risk of mortality score in predicting mortality in pediatric severe cerebral falciparum malaria cases - Kondekar, Alpana S; Ahmed, Maaz; Kondekar, Santosh (Indian Journal of Child Health, 2016)
Introduction: Pediatric risk of mortality score (PRISM-3) has been applied in pediatric intensive care settings for varied diagnoses. We planned to study the outcome when PRISM score is applied to a single clinical diagnosis. Objectives: To study the applicability of PRISM score in predicting mortality in pediatric severe cerebral malaria cases. Methodology: This was a retrospective analysis of severe cerebral malaria cases admitted to the pediatric intensive care unit over 3 years from 2009 to 2012 whose peripheral blood smear was positive for Plasmodium falciparum. Cases that presented with single seizure without altered sensorium were excluded. The PRISM scores, predicted mortality and observed mortality, were studied from demographic and clinical data. Results: Of the total 38 cases, 22 (57.8%) cases were females and 16 (42.10%) cases were males. There were 4 (10.52%) infants, 15 (39.4%) children from 1 to 5 years age and 19 (50%) cases were above 5 year age. A total of 14 cases, 36.84% had PRISM score ?10, whereas 16 cases (42.1%) had score 10-20 and 8 cases had scored above 20. Mean predicted mortality was 17.84%, whereas observed mortality was 21.05%. Observed mortality had statistically significant association with PRISM score and predicted mortality rate. Conclusion: PRISM score and the expected mortality rate were good indicators in expecting the outcome of severe cerebral malaria cases. PRISM score can be effectively applied in severe cerebral malaria cases in predicting the outcome.